(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Introduction: Cardiac rehabilitation (CR) typically comprises three or four phases. The final phase, phase III or IV, focusses on long-term exercise training and lifestyle modification to support secondary prevention of cardiovascular disease. Despite well-established benefits, there are currently no international consensus on how exercise training should be structured during this lifestyle-maintenance phase. This study aimed to map current organisational practices for exercise training across European countries during this phase of CR. Materials and Methods: A cross-sectional survey was conducted through the HEPA Promotion in Healthcare Settings Working Group of the HEPA Europe network. Representatives from 20 European countries completed a structured survey including programme guidelines (national/international), organisational models (facility types, staffing), participant stratification (risk levels, medical conditions), medical supervision protocols, and financial structures. Responses were pseudonymised and analysed descriptively to identify common practices and inter-country variations. Results: The findings revealed marked heterogeneity in delivery models, staffing, and patient inclusion. Only 55% of countries reported using national guidelines. Programmes were delivered across a range of settings, with non-profit (75%), public (55%), and for-profit (50%) providers (note that multiple options were possible). Sports facilities (80%) were more commonly used than medical settings (65%). Multidisciplinary teams typically involved physiotherapists (75%) and sports coaches (60%), with physician or nurse supervision in 65% of programmes. While 90% of programmes accepted low-risk patients and 95% accepted medium-risk patients, 70% also included high-risk individuals. Programmes commonly served those with cardiovascular risk factors (85%) and other chronic conditions (65%). Formal referral and medical clearance at 1st registration were required in 75%. Participant fees were charged in 80% of countries, ranging from €3 to €390 annually, with partial reimbursement available in 30%. Discussion: The lack of unified international guidance likely contributes to inconsistencies in access and quality of care. The predominance of national guidelines and variable medical supervision models may contribute to inconsistency in programme quality and patient outcomes. The frequent inclusion of high-risk participants in programmes without standardised medical oversight warrants particular attention. These findings provide a foundation for analysing the components of these approaches to better understand the feasibility and effects of lifelong CR strategies.